Shoot 'em up - Benattar, Rick.; Montford, Susan; Murphy, Don, 1962-; Davis, Michael, 1961 August 1-; Owen, Clive; Giamatti, Paul.; Bellucci, Monica, 1968-; McHattie, Stephen; Bryk, Greg.; New Line Cinema Corporation; Angry Films (Firm); New Line Home Entertainment (Firm); et al. (Burbank, CA : New Line Home Entertainment : Distributed by Warner Home Video, 2008)
Mr. Smith is not the best choice for looking after a child, yet after stumbling upon a blazing shoot-out, helping to birth a child amidst a hail of gunfire, and seeing the mother die before his eyes, he becomes determined to protect the young innocent at all costs. His adversaries are equally determined, and they will not stop until the newborn is dead.
Title from container.
Originally released as a motion picture in 2007.
Special features: Deleted scenes; "Ballet of bullets: the making of Shoot 'em up" featurette; all 15 minutes of writer/director Michael Davis original animatics.
Director of photography, Peter Pau ; editor, Peter Amundson ; music, Paul Haslinger ; costume designer, Denise Cronenberg ; production designer, Gary Frutkoff ; visual effects supervisor, Edward Irastorza.
Clive Owen, Paul Giamatti, Monica Bellucci, Stephen McHattie, Greg Bryk.
MPAA rating: R; pervasive strong bloody violence, sexuality and some language.
Keywords: Orphans -- Drama; Enemies -- Drama; Criminal behavior -- Drama; Prostitutes -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Films for the hearing impaired; Thriller -- Feature; Crime -- Feature; Feature films; Suspense films; Comedy films; Action and adventure films